DESIGN AND CATCH COMPOSITION OF DRIFT GILL NET IN BHAYANDER ESTUARY, MAHARASHTRA - Suraj Kumar Pradhan; S. Abuthagir Iburahim; S.S. Kamat; a. D. Nakhawa; Latha Shenoy (Journal of Indian Fisheries Association, 2017)
Estuary is one of the most important ecosystems on which many fishermen are dependent for their livelihood. Estuaries harbour many diversified species being the main breeding and feeding grounds for many aquatic species. The state of Maharashtra is bestowed with many estuarine areas and the Bhayander estuary situated in Thane district ranked second in the fish production from gill net sector. This paper deals with the design and catch composition of drift gill nets in the Bhayander estuary. Polyamide (PA) multifilament twine of diameter 0.23-0.26 was used for construction of net. Average mesh size of main webbing of drift gill nets was 90 mm. The total fleet length varied from 65 to 80 m. A total of 37 species of fish and cruslaeeares were recorded in the gill net. Major catch composition of drift gill nets consisted of Otolithoides biauritus (Bronze croaker), Johnius amblycephalus (Bearded croaker), Johnius macrorhynus (Big-snout croaker), Protonibea diacanthus (Black-spotted croaker), Mugil cephalus (Flat-head grey mullet), Plicofollis dussumieri (Black-tip Sea catfish) and Leptomelanosoma indicum (Indian thread fin).